2022
DOI: 10.1002/ece3.9036
|View full text |Cite
|
Sign up to set email alerts
|

“Jack‐of‐all‐trades” is parthenogenetic

Abstract: Sex is evolutionarily more costly than parthenogenesis, evolutionary ecologists therefore wonder why sex is much more frequent than parthenogenesis in the majority of animal lineages. Intriguingly, parthenogenetic individuals and species are as common as or even more common than sexuals in some major and putative ancient animal lineages such as oribatid mites and rotifers. Here, we analyzed oribatid mites (Acari: Oribatida) as a model group because these mites are ancient (early Paleozoic), widely distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 138 publications
0
4
0
Order By: Relevance
“…But in many species that encompass asexual lineages, when these lineages expand over large geographic areas, they are often assumed to be generalists without further analyses of environmental variables behind their distribution. This is the case in orabid mites (Maraun et al 2022) where geographic range sizes have been explicitly used as a proxy for specialisation. In this system, conclusions regarding asexual lineages' generalist ecological strategy have been drawn from their large range sizes but this was solely based on range size comparison of sexual and asexual populations.…”
Section: Discussionmentioning
confidence: 99%
“…But in many species that encompass asexual lineages, when these lineages expand over large geographic areas, they are often assumed to be generalists without further analyses of environmental variables behind their distribution. This is the case in orabid mites (Maraun et al 2022) where geographic range sizes have been explicitly used as a proxy for specialisation. In this system, conclusions regarding asexual lineages' generalist ecological strategy have been drawn from their large range sizes but this was solely based on range size comparison of sexual and asexual populations.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, there is no evidence that sexual oribatid mite species tend to be ecologically more variable than asexual species, at least in terms of number of occupied habitats (Cianciolo & Norton, 2006; Norton & Palmer, 1991). Indeed, asexual oribatid mite species tend to have larger geographic ranges, although widespread species might encompass many cryptic species with smaller ranges (Maraun et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, there is no evidence that sexual oribatid mite species tend to be ecologically more variable than asexual species, at least in terms of number of occupied habitats (Cianciolo & Norton, 2006;Norton & Palmer, 1991). Indeed, asexual oribatid mite species tend to have larger geographic ranges, although widespread species might encompass many cryptic species with smaller ranges (Maraun et al, 2022). It has been suggested that an inverse relationship between the proportion of sexual species and individuals and the density of individual mites across oribatid mite communities would support the structured resource hypothesis, assuming higher mite density implies higher resource abundance (Maraun et al, 2012(Maraun et al, , 2013(Maraun et al, , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Explanations relate to what might be considered their 'permissive' cytogenetics, as first posited by Wrensch et al 1993 (recently put in modern context by Archetti 2021): they are meiotic, and in a way that permits extended existence and, ultimately, speciation. In the past two-three decades dozens of research papers have examined many aspects of oribatid mite asexuality, including cytology, genetics, selective forces, phylogeny, and ecological ramifications, many from the laboratories of Michael Heethoff, Mark Maraun, andtheir students (e.g., Heethoff et al 2009, 2013;Maraun et al 2019Maraun et al , 2022 and most recently by Pequeno et al (2022).…”
mentioning
confidence: 99%